Preservation with Different Smoking Techniques to Extend the Shelf Life of “Urutan” Chicken - AA Made Semariyani; Sudiarta, I Wayan; Singapurwa , Ni Made Ayu Suardani; Suariani, Luh (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
“Urutan” chicken is one of the processed meat products processed through the manufacture of meat dough, fat and complete Balinese spices ("Basa Genep"). Extending the shelf life of “urutan” chicken can be done by smoking process either by cold smoking method or hot smoking. Smoke can preserve food ingredients due to the presence of acid, phenolic and carbonyl compounds. The method used in this study is Randomized Block Design (RBD) with a factorial pattern consisting of 2 factors, namely Factor I is Hot Smoking Technique consisting of 3 levels and Factor II is Smoking Time consisting of 4 levels so that 12 treatment combinations are obtained and 2 repetitions are carried out so that 24 experimental units are obtained. The parameters observed include phenol content, water content, ash content, fat content, protein content, Esherichia coli and Salmonella sp. Statistical analysis shows that smoking time has a significant effect (sig <0.05) on the phenol content of “urutan” chicken, but does not have a significant effect (sig> 0.05) on the fat and protein content of “urutan” chicken. The fat content of “urutan” chickens in the smoking duration treatment at a temperature of 100 ° C ranged from 9.798 - 11.870%. The lowest fat content was obtained in 2 hours of smoking, which was 9.798% which was not significantly different from other treatments. The protein content of “urutan” chickens in the smoking treatments of 0.5, 1, 1.5 and 2 hours ranged from 11.788 -12.197%. The smoking duration did not have a significant effect on the protein content of “urutan” chickens, which was probably because the smoking duration of 0.5 -2 hours had not denatured the protein sequence. The phenol content of “urutan” chickens in the smoking treatments of 0.5, 1, 1.5 and 2 hours ranged from 0.206 - 0.312%. The highest phenol content was obtained in 2 hours of smoking at a smoking temperature of 100 ° C, which was 0.312%. The results showed that the longer the smoking, the higher the phenol content of “urutan” chickens. The lowest pH value was obtained in the 100 °C 2-hour smoking treatment of 5.16, which was significantly different from other treatments. The highest water content was obtained in the 100 °C 2-hour temperature treatment of 63.19%, which was significantly different from other treatments